Exploring an Africentric High School Cohort from the Parents’ Perspectives - Hudson, Karen; Hamilton-Hinch, Barb; Harkins, Mary Jane; Barchuk, Zhanna; Seselja, Diana (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
In Canada, the Black population is the third-largest racially visible group, yet students of African descent continue to face inequities in Canadian school systems. Students of African descent can benefit from learning from an Africentric perspective that cultivates their well-being and achievement while centring their lived experience as a person of African descent. As research demonstrates the significance of parental involvement in Africentric education, the purpose of this study was to explore an Africentric High School Cohort from the perspective of parents of the students of African descent in this Cohort. Based on the conceptual framework of Nguzo Saba, the theoretical framework of Africentric education, and critical race theory, a thematic analysis of the findings was conducted. The findings are discussed under the themes of parental engagement, positive youth development, and addressing challenges. Recommendations are suggested for future Africentric cohorts.